Configuration, Control and Monitoring of a FlexRay Cluster via TCP/IP - Nikolay Stoitsov (Hochschule für angewandte Wissenschaften Hamburg, 2018)
This bachelor thesis describes the development and implementation design of a software application, used to perform initial configuration, control and monitoring tasks of a FlexRay node. The communication is realized by hard-wired cables and a network switch and is based on the TCP/IP protocol.